Dysregulation of miR-375/AEG-1 Axis by Human Papillomavirus 16/18-E6/E7 Promotes Cellular Proliferation, Migration, and Invasion in Cervical Cancer - Jayamohan, Sridharan; Kannan, Maheshkumar; Moorthy, Rajesh Kannan; Rajasekaran, Nirmal; Jung, Hun Soon; Shin, Young Kee; Arockiam, Antony Joseph Velanganni (Frontiers in Oncology, 2019)
Cervical Cancer (CC) is a highly aggressive tumor and is one of the leading causes of cancer-related deaths in women. miR-375 was shown to be significantly down-regulated in cervical cancer cells. However, the precise biological functions of miR-375 and molecular mechanisms underlying its action in CC are largely unknown. miR-375 targets were predicted by bioinformatics target prediction tools and validated using luciferase reporter assay. Herein, we investigated the functional significance of miR-375 and its target gene in CC, to identify potential new therapeutic targets. We found that miR-375 expression was significantly downregulated in CC, and astrocyte elevated gene-1 (AEG-1) was identified as a target of miR-375. Our results also showed that ectopic expression of miR-375 suppressed CC cell proliferation, migration, invasion, angiogenesis and increased the 5-fluorouracil-induced apoptosis and cell cycle arrest in vitro. In contrast, inhibition of miR-375 expression significantly enhanced these functions. Furthermore, HPV - 16 E6/E7 and HPV- 18 E6/E7 significantly down-regulates miR-375 expression in CC. HPV 16/18-E6/E7/miR-375/AEG-1 axis plays an important role in the regulation of cell proliferation, migration, and invasion in CC. Therefore, targeting miR-375/AEG-1 mediated axis could serve as a potential therapeutic target for CC.